Effect of microstructure on chain flexibility and glass transition temperature of polybenzofulvene. (6th January 2021) - Wang, Huiqun; Wang, Weiyu; Lu, Wei; Osa, Masashi; Kang, Nam-Goo; Hong, Kunlun; Mays, Jimmy
Abstract: Polybenzofulvene (PBF) is a polydiene with a very high glass transition temperature ( T g ), which makes it a potential candidate for use as the hard block for high-temperature thermoplastic elastomer applications. The T g s of polydienes are known to be related to chain flexibility. However, no studies have been reported that correlate the chain flexibility to the microstructure of PBF. Herein, we present a study of solution properties of linear PBFs with narrow molacular weight dispersity and having 1, 2-addition ranging from 23% to 99%. The materials were prepared by living anionic polymerization under different conditions. Specifically, the chain flexibility as defined by the Flory's characteristic ratio, C ∞, and dependence of chain flexibility on microstructure by combined measurements of intrinsic viscosity and molecular weight using triple-detector size exclusion chromatography (SEC) is studied. The persistence lengths ( l p ) and chain diameters ( d B ) were also estimated using the touched-bead wormlike chain model. To the best of our knowledge, the characteristic ratio of PBF is found to be the highest of all polydienes that have been reported so far. Graphical abstract: Image 1 Highlights: The effect of microstructure on chain flexibility and glass transition temperature of polybenzofulvene (PBF) was studied. The solution properties of PBF were investigated by using SEC with triple-detector. Characteristic ratio, glass transition temperature, and persistence length of the PBF increase with 1, 2-microstructures. The characteristic ratio of PBF is found to be the highest of all polydienes that have been reported so far.